2020
DOI: 10.7150/thno.42069
|View full text |Cite
|
Sign up to set email alerts
|

PRL-3 facilitates Hepatocellular Carcinoma progression by co-amplifying with and activating FAK

Abstract: Background: In addition to protein tyrosine kinases, accumulating evidence has shown that protein tyrosine phosphatases (PTPs) are suitable therapeutic targets in cancer. PRL-3 is a PTP member that has been well studied in many malignant tumours. The goal of the present study was to elucidate the role of PRL-3 in hepatocellular carcinoma (HCC), which remains largely unknown. Methods: Bioinformatic and immunohistochemical analyses were performed to analyse PRL-3 expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…It is reported that CDK4 and Phosphoinositide 3-kinase enhancer (PIKE-A) are co-localized on chromosomal 12q13.1-14 and co-amplified in glioblastoma and form a protein complex with each other to promote tumorigenesis ( 38 ). Similar mechanism was found for ACTL6A and p63 in head and neck squamous cell carcinoma ( 7 ), PRL-3 and FAK in hepatocellular carcinoma ( 39 ). Differently, S100A7, S100A8 and S100A9 are co-amplified on chromosome 1q21.3 in breast cancer, have similar functions and cooperate with each other to induce target protein phosphorylation leading to tumor recurrence and chemoresistance ( 6 ).…”
Section: Discussionsupporting
confidence: 73%
“…It is reported that CDK4 and Phosphoinositide 3-kinase enhancer (PIKE-A) are co-localized on chromosomal 12q13.1-14 and co-amplified in glioblastoma and form a protein complex with each other to promote tumorigenesis ( 38 ). Similar mechanism was found for ACTL6A and p63 in head and neck squamous cell carcinoma ( 7 ), PRL-3 and FAK in hepatocellular carcinoma ( 39 ). Differently, S100A7, S100A8 and S100A9 are co-amplified on chromosome 1q21.3 in breast cancer, have similar functions and cooperate with each other to induce target protein phosphorylation leading to tumor recurrence and chemoresistance ( 6 ).…”
Section: Discussionsupporting
confidence: 73%
“…Deregulation of phosphatases contributes to tumorigenesis and tumor progression, so phosphatases are exciting targets for HCC drug discovery [25]. As for the role of phosphatase in HCC, our previous studies have reported that PRL-1 promotes HCC cell migration and invasion through endothelial-mesenchymal transition induction [26], and that PRL-3 facilitates HCC progression by coamplifing with FAK as well as enhancing FAK phosphorylation [27]. Inositol polyphosphate 5-phosphatases are a group of phosphatases involved in regulating phosphorylation of phosphoinositide.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of phosphatases contributes to tumorigenesis and tumor progression, so phosphatases are exciting targets for HCC drug discovery [25]. As for the role of phosphatase in HCC, our previous studies have reported that PRL-1 promotes HCC cell migration and invasion through endothelial-mesenchymal transition induction [26], and that PRL-3 facilitates HCC progression by co-ampli ng with FAK as well as enhancing FAK phosphorylation [27]. Inositol polyphosphate 5-phosphatases are a group of phosphatases involved in regulating phosphorylation of phosphoinositide.…”
Section: Discussionmentioning
confidence: 99%